The Effect of Biostarter Addition on Kudzu (Pueraria Javanica) Compost to Nutrient Content and N Adsoprtion of Mustard (Brassica Juncea L.) - Nurlita Hartanti (University of Jember, 2023)
Compost fertilizer is very influential on the nutrient status of the soil and plants. Giving compost fertilizer will also have a good effect on the growth and development of mustard plants. This study aims to determine the effect of the addition of biostarter on compost fertilizer to N-total and N nutrient absorption on mustard plants. The experiment was structured using factorial randomized group design. The method in this study using compost analysis,soil analysis, and plant analysis. The results showed that the nine samples have different nutrient content and nutrient nutrient absorption resulting in different effects on soil and mustard plants. Nitrogen in the soil greatly affects the N nutrient absorption on plants, the two parameters have a positive correlation which means directly proportional. Nitrogen absorbed by plants affects N-total levels in plants. N levels in plants and soil is very influential on the color of the leaves of mustard plants. Through the nutrient levels can be known proper fertilization recommendations for mustard plants. Based on the analysis of nutrient levels in soil and plants known fertilizer recommendations in nine samples with the addition of biostarter in kudzu compost and fertilizer doses.